Influence of Profitability, Leverage, and Environmental Costs On Environmental Performance - Wihandoko, Imanuel; Zakaria, Adam; Ulupui, I Gusti Ketut Agung (LPPM Universitas Negeri Jakarta, 2022)
This study intends to determine the impact of profitability, leverage, and environmental costs on environmental performance. Profitability is proxied by the ratio of net income to total assets, leverage is proxied by the ratio of debt to equity. The population of this research is non-financial companies listed on the Indonesia Stock Exchange (IDX) and PROPER witha period of 2017-2020. The method of determining the sample used the principle of purposive sampling and obtained a sample of thirteen companies so that the total observations were fifty-two. Eviews 8 software is used in the study of the evidence for presumption testing by utilizing the panel regression analysis. The research results show that profitability, leverage, and environmental costs have a negative and insignificant effect on environmental performance.